2023
DOI: 10.1021/acsptsci.3c00134
|View full text |Cite
|
Sign up to set email alerts
|

Deuremidevir and Simnotrelvir–Ritonavir for the Treatment of COVID-19

Abstract: Deuremidevir hydrobromide tablets and simnotrelvir tablets/ritonavir tablets (co-packaged) were approved by the Chinese National Medical Products Administration for the treatment of mild to moderate COVID-19 in January 2023. Both formulations contain small-molecule anti-SARS-CoV-2 agents. Deuremidevir, an oral nucleoside analog, is a broad-spectrum virus replication inhibitor targeting the highly conserved RNAdependent RNA polymerase. Simnotrelvir−ritonavir is a copackaged combination drug consisting of simnot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…For instance, the combination of lopinavir and ritonavir, commonly used for HIV treatment, has shown inhibitory activity on of COVID-19 protease in in vitro experiments, but has not demonstrated significant efficacy in clinical trials [ 28 ]. Although Paxlovid, an FDA-approved SARS-CoV-2 Mpro protease inhibitor, shows promise, it is still constrained by limitations such as supply constraints, high cost, and limited clinical evidence [ 29 ]. Therefore, this study aims to identify new active compounds from traditional Chinese medicine (TCM) to expand the range of antiviral therapeutic options against viral proteases.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the combination of lopinavir and ritonavir, commonly used for HIV treatment, has shown inhibitory activity on of COVID-19 protease in in vitro experiments, but has not demonstrated significant efficacy in clinical trials [ 28 ]. Although Paxlovid, an FDA-approved SARS-CoV-2 Mpro protease inhibitor, shows promise, it is still constrained by limitations such as supply constraints, high cost, and limited clinical evidence [ 29 ]. Therefore, this study aims to identify new active compounds from traditional Chinese medicine (TCM) to expand the range of antiviral therapeutic options against viral proteases.…”
Section: Discussionmentioning
confidence: 99%
“…RdRp is highly conserved in the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and is an excellent target for the development of anti-SARS-CoV-2 agents Vicenti et al, 2021;Zhu, 2023a). Nucleoside analogs were considered candidate drugs for the treatment of coronavirus disease 2019 (COVID-19), and several nucleoside analogs were identified as promising anti-SARS-CoV-2 drugs based on satisfactory results of preclinical trials .…”
Section: Discussionmentioning
confidence: 99%
“…302 The dithia-7-azaspiro[4.4]nonane derivative 80 is a strong SARS-CoV-2 M pro inhibitor which was developed by Simcere Pharmaceutical. In association with ritonavir, 303 it has also been granted conditional market approval in China under the name Xiannuoxin/simnotrelvir 304–306 and the results of phase 1 clinical trials (NCT05339646) were reported recently. 307 The undisclosed SARS-CoV-2 M pro inhibitor ALG-097558 is developed by Aligos therapeutics, possibly without a co-administration of ritonavir and phase 1 clinical trials have been initiated (NCT05840952).…”
Section: Inhibitors Of the Sars-cov-2 Main Proteasementioning
confidence: 99%